2020
DOI: 10.1007/s40430-020-2237-2
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and tribological characteristics of boron carbide reinforcement of AA6061 matrix composite

Abstract: The use of boron carbide-reinforced aluminium matrix composites has grown rapidly in critical applications of aerospace industries, automotive sectors, military, and nuclear engineering. However, boron carbide reinforcement within AA6061 alloy is worthy of investigation in terms of its mechanical and tribological properties. Novel aluminium matrix composites were developed with three different reinforcements (i.e. 5, 10, and 15 wt% of B 4 C) by using the stir casting process. The developed samples were then te… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
19
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(19 citation statements)
references
References 30 publications
0
19
0
Order By: Relevance
“…al., 2020 [29], almost all work showed an increase in hardness by the addition of B4C in Al matrix based hybrid composites [10], [30][31]. The fluctuation in hardness value in the work presented by the group [Hynes et. al., 2020] might be due to the imropoer mixing of B4C particles.…”
Section: Indentation Test Results Of Aa6061 Hybrid Compositesmentioning
confidence: 99%
“…al., 2020 [29], almost all work showed an increase in hardness by the addition of B4C in Al matrix based hybrid composites [10], [30][31]. The fluctuation in hardness value in the work presented by the group [Hynes et. al., 2020] might be due to the imropoer mixing of B4C particles.…”
Section: Indentation Test Results Of Aa6061 Hybrid Compositesmentioning
confidence: 99%
“…al., 2020 [29], almost all work showed an increase in hardness by the addition of B4C in Al matrix based hybrid composites [10], [30][31]. The fluctuation in hardness value in the work presented by the group [Hynes et. al., 2020] might be due to the imropoer mixing of B4C particles.…”
Section: Indentation Test Results Of Aa6061 Hybrid Compositesmentioning
confidence: 99%
“…In addition, it has stable hightemperature strength and can absorb neutrons [5][6][7][8][9]. B 4 C has been added to the matrix of many metal materials, as a strengthening phase to improve their performance [10][11][12][13][14][15][16]. For example, Lyu et al [10] added B 4 C particles into a Q235 steel substrate and found that the wear resistance could be greatly improved.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, Joshi et al [12] introduced B 4 C particles into a magnesium (Mg) alloy matrix, and found that the wear properties and hardness of B 4 C/Mg composites were largely improved. Additionally, Hynes et al [15] found that the mechanical properties of the AA6061 matrix composites were enhanced by adding B 4 C reinforcement, and the wear resistance was also superior. At the same time, Aherwar et al [16] studied the impact of B 4 C and porcelain particulates on aluminum (Al) matrix composite properties.…”
Section: Introductionmentioning
confidence: 99%